2016
DOI: 10.5847/wjem.j.1920-8642.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting psychological morbidity in emergency medicine practitioners

Abstract: BACKGROUND: Assessing and evaluating mental health status can provide educational planners valuable information to predict the quality of physicians' performance at work. These data can help physicians to practice in the most desired way. The study aimed to evaluate factors affecting psychological morbidity in Iranian emergency medicine practitioners at educational hospitals of Tehran. METHODS:In this cross sectional study 204 participants (emergency medicine residents and specialists) from educational hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
2
7
1
1
Order By: Relevance
“…The present study found a positive relationship between professional experience and the social dysfunction scale of GHQ-28, contrary to that found in other research ( 3 ) . This finding can be explained by two facts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study found a positive relationship between professional experience and the social dysfunction scale of GHQ-28, contrary to that found in other research ( 3 ) . This finding can be explained by two facts.…”
Section: Discussioncontrasting
confidence: 99%
“…The proportion of possible psychiatric cases among the health professionals studied was 32.3%, similar to that obtained in another study ( 3 ) . The problem-centered coping was the most commonly used strategy, which could explain the relative low morbidity found.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Health-care professionals have higher psychological morbidity rates than that of the general population (Momeni, Fahim, Vahidi, Nejati, & Saeedi, 2016). In particular, nurses have a stressful job caring for patients at risk (e.g., comorbidity, polypharmacy, low health literacy) (Tessa et al., 2011).…”
Section: Background and Purposementioning
confidence: 99%
“…This can also lead to sleep disorders and fatigue during clinical shifts. Night-shift work is accompanied by deleterious physical and psychological problems including insomnia, [1] hypertriglyceridemia, [2] hypertension, [3] coronary artery disease, [4] depression, [5] alcohol or drug abuse [6] and gastrointestinal disorders. [7] Sleep deprivation can have a bad effect on physician gestalt and patient safety.…”
Section: Introductionmentioning
confidence: 99%